Pediculosis by Haematopinus tuberculatus in water buffaloes (Bubalus bubalis) - Ojeda-Robertos, Nadia Florencia; Peralta-Torres, Jorge Alonso; López-Hernández, Keyla Gretel; Chay-Canul, Alfonso Juventino; Ojeda-Chi, Melina Maribel; Rodríguez-Vivas, Roger Iván (Ecosistemas y Recursos Agropecuarios, 2022)
The objective was to identify the species, prevalence, clinical manifestations and two treatments to control an outbreak of lice in water buffalo in the tropics of Mexico. A prospective descriptive observational study was carried out, with weekly visits for two months to a buffalo farm. A total of 300 female buffaloes were inspected to determine the prevalence and species of louse. The level of infestation by adult lice and skin lesions (n = 40) were determined, and two treatments were applied in two groups (n = 10), cypermethrin (15%) + dichlorvos (30%) was applied by spray and ivermectin 1% subcutaneous route (0.2 mg/kg1 of bw). The prevalence of the infestation was 100%, the louse was identified as Haematopinus tuberculatus. Adult lice infestations were low in 60% of buffaloes and 95% in calves. The efficacy of the insecticides was 80% in buffaloes and 100% in calves.